Interplanetary mesoscale observatory (InterMeso): A mission to untangle dynamic mesoscale structures throughout the heliosphere - Allen, Robert C.; Smith, Evan J.; Anderson, Brian J.; Borovsky, Joseph E.; Ho, George C.; Jian, Lan; Krucker, Sämuel; Lepri, Susan; Li, Gang; Livi, Stefano; Lugaz, Noé; Malaspina, David M.; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Mesoscale dynamics are a fundamental process in space physics, but fall within an observational gap of current and planned missions. Particularly in the solar wind, measurements at the mesoscales (100s RE to a few degrees heliographic longitude at 1 au) are crucial for understanding the connection between the corona and an observer anywhere within the heliosphere. Mesoscale dynamics may also be key to revealing the currently unresolved physics regulating particle acceleration and transport, magnetic field topology, and the causes of variability in the composition and acceleration of solar wind plasma. Studies using single-point observations do not allow for investigations into mesoscale solar wind dynamics and plasma variability, nor do they allow for the exploration of the sub-structuring of large-scale solar wind structures like coronal mass ejections (CMEs), co-rotating/stream interaction regions (CIR/SIRs), and the heliospheric plasma sheet. To address this fundamental gap in our knowledge of the heliosphere at these scales, the Interplanetary Mesoscale Observatory (InterMeso) concept employs a multi-point approach using four identical spacecraft in Earth-trailing orbits near 1 au. Varying drift speeds of the InterMeso spacecraft enable the mission to span a range of mesoscale separations in the solar wind, achieving significant and innovative science return. Simultaneous, longitudinally-separated measurements of structures co-rotating over the spacecraft also allow for disambiguation of spatiotemporal variability, tracking of the evolution of solar wind structures, and determination of how the transport of energetic particles is impacted by these variabilities.